Profiling Inter‐Specific and Inter‐Estuarine Variation in Per‐ and Polyfluoroalkyl Substances Across Two Recreational Fishing Havens - Matthew D. Taylor; Julian M. Hughes; Jeff Murphy; Faith A. Ochwada‐Doyle (Fisheries Management and Ecology, 2025)
Contamination of estuaries with per‐ and polyfluoroalkyl substances (PFAS), such as perfluorooctane sulfonate (PFOS), may impact recreational fishers who consume their catch. However, the presence and concentration of PFAS across commonly harvested estuarine taxa is rarely quantified. We used data from a state‐wide survey of recreational fishers to design and conduct a sampling program for assessing PFAS contamination across two recreational fishing havens (Lake Macquarie and Botany Bay, New South Wales, Australia). Perfluorodecanoic acid (PFDA) and PFOS were the primary contaminants in edible tissues of recreationally harvested species, and concentrations were highly variable. In Lake Macquarie, all samples were below screening criteria, as were invertebrates in both estuaries. In Botany Bay, some fish exceeded screening criteria, but the most frequently harvested recreational species had the lowest concentrations of all fish across both estuaries. Ecological factors likely contributed to substantial variation in PFAS accumulation levels among different recreational species. Recreational fisheries surveys provide a solid foundation to frame investigations of exposure risk and support the development of spatially tailored dietary advice.